Microcystin-LR induced liver injury in mice and in primary human hepatocytes is caused by oncotic necrosis. (January 2017) - Woolbright, Benjamin L.; Williams, C. David; Ni, Hongmin; Kumer, Sean C.; Schmitt, Timothy; Kane, Bartholomew; Jaeschke, Hartmut
Abstract: Microcystins are a group of toxins produced by freshwater cyanobacteria. Uptake of microcystin-leucine arginine (MC-LR) by organic anion transporting polypeptide 1B2 in hepatocytes results in inhibition of protein phosphatase 1A and 2A, and subsequent cell death. Studies performed in primary rat hepatocytes demonstrate prototypical apoptosis after MC-LR exposure; however, no study has directly tested whether apoptosis is critically involved in vivo in the mouse, or in human hepatocytes. MC-LR (120 μg/kg) was administered to C57BL/6J mice and cell death was evaluated by alanine aminotransferase (ALT) release, caspase-3 activity in the liver, and histology. Mice exposed to MC-LR had increases in plasma ALT values, and hemorrhage in the liver, but no increase in capase-3 activity in the liver. Pre-treatment with the pan-caspase inhibitor z-VAD-fmk failed to protect against cell death measured by ALT, glutathione depletion, or hemorrhage. Administration of MC-LR to primary human hepatocytes resulted in significant toxicity at concentrations between 5 nM and 1 μM. There were no elevated caspase-3 activities and pretreatment with z-VAD-fmk failed to protect against cell death in human hepatocytes. MC-LR treated human hepatocytes stained positive for propidium iodide, indicating membrane instability, a marker of necrosis. Of note, both increases in PI positive cells, and increases in lactate dehydrogenase release, occurred before the onset of complete actin filament collapse. In conclusion, apoptosis does not contribute to MC-LR-induced cell death in the in vivo mouse model or in primary human hepatocytes in vitro . Thus, targeting necrotic cell death mechanisms will be critical for preventing microcystin-induced liver injury. Highlights: Microcystin induced liver injury causes significant necrosis and hemorrhage in mice. Caspase inhibition fails to protect against microcystin induced liver injury in mice. There is limited caspase activation in human hepatocytes exposed to microcystin-LR. Caspase inhibitors do not protect against microcystin in human hepatocytes. Cell death via necrosis precedes cytoskeletal disruption.